2002
DOI: 10.1038/sj.jea.7500204
|View full text |Cite
|
Sign up to set email alerts
|

The effect of relevant genotypes on PAH exposure-related biomarkers

Abstract: Polycyclic aromatic hydrocarbons ( PAHs ) in coke oven emissions cause a cancer risk to humans. In a comprehensive biomonitoring study among Estonian coke oven workers, we looked at the effect of genetic polymorphisms in metabolic enzymes on urinary mutagenicity, 1 -hydroxypyrene ( 1 -OHP ) concentration in urine, and aromatic DNA adducts in white blood cells ( WBCs ). Coke oven workers were sampled twice ( samplings I and II ), and controls only once at the time of sampling I. Urinary mutagenicity was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 55 publications
5
20
0
Order By: Relevance
“…Other potential confounders, such as age and Caucasian ethnicity, had no relevant effect on hydroxyphenanthrenes in this study (13). In addition, genetic polymorphisms may modulate the individual levels of PAH metabolites (46)(47)(48)(49)(50)(51)(52). We found no clear effect of various sequence variations on the metabolite levels in our study as published elsewhere (13).…”
Section: Discussionsupporting
confidence: 47%
“…Other potential confounders, such as age and Caucasian ethnicity, had no relevant effect on hydroxyphenanthrenes in this study (13). In addition, genetic polymorphisms may modulate the individual levels of PAH metabolites (46)(47)(48)(49)(50)(51)(52). We found no clear effect of various sequence variations on the metabolite levels in our study as published elsewhere (13).…”
Section: Discussionsupporting
confidence: 47%
“…Although several lines of evidence showed that variant genotypes of cytochrome P450 such as CYP1A1 and CYP2E1 could modify the metabolism of PAH in coke-oven workers (24)(25)(26), other studies reported no correlations between cytochrome P450 polymorphism and urinary 1-OHP level (9,(27)(28)(29). Therefore, it is hard to interpret the relation between cytochrome P450 polymorphism and urinary 1-OHP level.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferase (GSTM1) genotype has been shown to influence the association between PAH exposure and 1-OHPG levels in urine (25,40). Several genetic polymorphisms, including a cytochrome P450 variant (CYP1A1), glutathione S-transferases (GSTT1 and GSTM1), N-acetyltransferase (NAT2), and an epoxide hydrolase (mEH3), have also been related to variation in 1-hydroxypyrene levels in urine (42,(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%